(untitled) (Progressive Agriculture, 2013)
To observe the effectiveness of short time in-pond nursery of post larvae (PL) on the survival rate and production of shrimp (Penaeus monodon) under modified improved culture system, an experiment was conducted in earthen ponds at Brackishwater Station of Bangladesh Fisheries Research Institute, Khulna. Results of the experiment revealed that short time in-pond nursery of PL provided the significantly higher (p<0.05) survival rate (58%) than direct stocking of PL (47.81%) in the rearing pond. In-pond nursery of PL provided 9.95% better survival rate than direct stocking. The production of shrimp was 661 kg/ha under in-pond nursery of PL and it was 534 kg/ha under direct stocking of PL in rearing ponds. The production of shrimp was also significantly higher (p<0.05) under in-pond nursery system than direct stocking of PL in rearing ponds. Final weight gain and Food Conversion Ratio (FCR) values were similar in both the treatments. Water quality parameters in both stocking systems were insignificant and it was within the range of shrimp culture. In this study, the increment in production under in-pond nursery system was mainly due to the increase of survival rate in the respective treatment was ascertained. DOI: http://dx.doi.org/10.3329/pa.v19i2.16958 Progress. Agric. 19(2): 167 - 175, 2008